Imprisonment and rights : Effects of female inmates’ communicative challenges on reintegration in Zimbabwe (Namibian Journal of Linguistics, Literature and Communication Studies, 2026)
This study investigates the impact of communication challenges on female inmates' successful reintegration post-imprisonment in Zimbabwe. Through qualitative research, including in-depth interviews, observations, and document analysis, the study examines the extent to which the Zimbabwe Prisons and Correctional Service (ZPCS) facilitates effective communication between female inmates and their families. Findings reveal that despite constitutional mandates, the ZPCS's failure to support effective communication undermines inmate preparation for reintegration. Challenges such as limited visits, ill-treatment, and resource scarcity hinder female inmates' ability to maintain family ties and acquire necessary skills for successful reintegration. The study calls for comprehensive interventions to address these challenges and empower female inmates for a smoother transition back into society.
Keywords: Communication; recidivism; ZPCS; rehabilitation; reintergration; female inmates